En route vers la désinvisibilisation… et la dévulnérabilisation ? - Yann Descamps (Genre & Histoire)
Sports Mangas are very popular cultural artefacts both in Japan and France. In these works, just like in the media coverage of sport in these two countries, women athletes stand in the shadows of their male counterparts, who are constructed as undisputed, hegemonic athletic ideals. Moreover, disabled women athletes are widely invisibilized in sports manga, except for one three-volume series published in the wake of the Tokyo Paralympics, Blade Girl: Kataashi no Runner (Running Girl. Ma course vers les Paralympiques in French) which portrays a disabled woman athlete – a figure who faces many discriminations. Narumi Shigematsu’s work contributes to a process of disinvisibilization of people who face multiple discriminations both in society and the world of sport. This study analyzes this new representation by highlighting its historical, cultural, and political significance in order to understand the stakes.